Description of the larvae of Tapinoma melanocephalum (Hymenoptera: Formicidae) - De Jesus, Carlos Massuretti [UNESP]; Fox, Eduardo Gonalves Paterson [UNESP]; Solis, Daniel Russ [UNESP]; Yabuki, Antonio Teruyoshi [UNESP]; Rossi, Monica Lanzoni; Bueno, Odair Correa [UNESP] (De Gruyter, 2010)
Morphological descriptions of the 4 instars of the ghost-ant Tapinoma melanocephalum Fabricius are presented along with illustrations and comparisons with other species of the same genus. Instars were similar, differing only in body length. The analyzed larvae presented many characteristics in common with other Tapinoma Frster larvae, such as: dolichoderoid body and mandibles, 9 pairs of spiracles, the presence of a terminal boss, and scarce body and head setae, all simple and short. We observed the following differences from other previous descriptions: the presence of a subapical mandibular tooth, setaceous sensilla on the medial anterior surface of the labrum, and fewer sensilla on maxillary and labial palps.
Keywords: Dolichoderinae; ghost-ant; larval description; tramp species